2015
DOI: 10.1039/c5cp00794a
|View full text |Cite
|
Sign up to set email alerts
|

Protein motions and dynamic effects in enzyme catalysis

Abstract: The role of protein motions in promoting the chemical step of enzyme catalysed reactions remains a subject of considerable debate. Here, a unified view of the role of protein dynamics in dihydrofolate reductase catalysis is described. Recently the role of such motions has been investigated by characterising the biophysical properties of isotopically substituted enzymes through a combination of experimental and computational analyses. Together with previous work, these results suggest that dynamic coupling to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
69
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(75 citation statements)
references
References 126 publications
(299 reference statements)
4
69
0
Order By: Relevance
“…Small, non‐conjugated substrates are “good” substrates, resulting in higher k cat constants than those for the bulky ones. In line with our proposal,3b, 13 dynamic coupling was found to be less significant for small, non‐conjugated substrates at 20 °C ( k cat LE / k cat HE ≤1.2; Figure 3 C). Sampling an ideal configuration for hydride transfer is likely less energetically demanding for “good” substrates where less reorganization of the active site residues is required, and thus they lead to higher values of k cat and lower enzyme KIEs (Figure 3 C and Tables S8 and S9).…”
supporting
confidence: 90%
See 1 more Smart Citation
“…Small, non‐conjugated substrates are “good” substrates, resulting in higher k cat constants than those for the bulky ones. In line with our proposal,3b, 13 dynamic coupling was found to be less significant for small, non‐conjugated substrates at 20 °C ( k cat LE / k cat HE ≤1.2; Figure 3 C). Sampling an ideal configuration for hydride transfer is likely less energetically demanding for “good” substrates where less reorganization of the active site residues is required, and thus they lead to higher values of k cat and lower enzyme KIEs (Figure 3 C and Tables S8 and S9).…”
supporting
confidence: 90%
“…The difference in the rate constants measured with the “light” and “heavy” enzyme are caused by changes in the recrossing coefficients γ 2b, 3b, 12. Indeed, because our simulations were carried out using an antisymmetric combination of the distances of the hydride to donor and the acceptor atoms as distinguished reaction coordinate, γ incorporates the effect of the remaining degrees of freedom of both the protein and substrate, which accounts for the additional friction observed on the distinguished reaction coordinate.…”
mentioning
confidence: 99%
“…kcat) remains an open question in enzymology. [1][2][3] There has been good progress in establishing the role of ms-ns dynamics such as loop opening/closing during enzyme turnover using NMR approaches, 4,5 but direct evidence for the coupling of faster (sub-ns) dynamics to chemistry remains illusive and controversial 6,7 and is based in part on the anomalous temperature dependencies of kinetic isotope effects (KIEs; e.g. kH/kD) on enzyme catalyzed H-transfer reactions.…”
Section: Introductionmentioning
confidence: 99%
“…Probably, the dynamical contribution to the catalytic power of enzymes is the subject most debate currently in enzyme catalysis. [71][72][73][74][75][76] This idea, introduced by several authors [77][78][79][80] is based that the dynamical effects require deviations from the TST, and the deviation of the rate constant is obtained by means of a transmission coefficient. Although several studies support the idea that dynamical effects contribute to the enzyme catalysis, 59,63,[81][82][83][84] Warshel and co-workers in several reviews about the role of dynamics in enzyme catalysis 71,73,76 concluded that no dynamical effect has ever been experimentally shown to contribute to catalysis and from theoretical studies, the contributions are small or negligible.…”
Section: And As Warshel Andmentioning
confidence: 99%